Let f ( x ) = 3 x + 5 and g ( x ) = 3 x 2 + 3 x . After simplifying, ( f ∘ g ) ( x ) =
![Let f x 3 x 5 and g x 3 x 2 3 x After simplifying f g x class=](https://us-static.z-dn.net/files/d18/ce018bd0ae2e180f371ed92e69fc8c87.png)
Answer
Explanation
Given:
[tex]f(x)=3x+5[/tex][tex]g(x)=3x^2+3x[/tex]To determine (f º g)(x), we plug in the value of g(x) into f(x) as shown below:
[tex]\begin{gathered} (f\circ g)(x)=f(g(x)) \\ =f(3x^2+3x) \\ =3(3x^2+3x)+5 \\ Simplify \\ (f\circ g)(x)=9x^2+9x+5 \end{gathered}[/tex]Therefore, the answer is:
[tex](f\circ g)(x)=9x^{2}+9x+5[/tex]